Strategies of School Principals in Improving PAI Teachers' Performance Through the Merdeka Mengajar Platform at SMP Negeri 5 Jawai (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the lack of teacher performance in utilizing the Merdeka Mengajar platform application. Therefore, PAI teachers are required to be able to operate the Merdeka Mengajar platform application. This study aims to obtain clear information about: 1) Planning the Merdeka Mengajar platform in improving the performance of PAI teachers at SMP Negeri 5 Jawai. 2) Steps of the Merdeka Mengajar platform in improving the performance of PAI teachers at SMP Negeri 5 Jawai. 3) Evaluation of the Merdeka Mengajar platform in improving the performance of PAI teachers at SMP Negeri 5 Jawai. The subjects of this research are PAI teachers and the principal of SMP Negeri 5 Jawai. To obtain data related to the research focus, researchers conducted interviews, observations, and documentation. The data validity checking techniques used are: 1) Triangulation technique, 2) Member Check technique. The results of the research can be concluded: 1) Planning the Merdeka Mengajar platform in improving the performance of PAI teachers at SMP Negeri 5 Jawai is done by preparing activity programs, scheduling, preparing materials based on the Merdeka Mengajar platform application, and evaluating the program implementation. 2) Steps of the Merdeka Mengajar platform in improving the performance of PAI teachers at SMP Negeri 5 Jawai are done by: forming facilitators, analyzing the level of school readiness, designing dimensions to be used, themes, time allocation, and compiling project modules and reporting strategies, introducing and guiding teachers who have not been able to operate the Merdeka Mengajar platform application. 3) Evaluation of the Merdeka Mengajar platform in improving the performance of PAI teachers at SMP Negeri 5 Jawai includes: increased teacher engagement in using various PMM features, improved pedagogical and professional competence of teachers, increased ability of teachers to adopt innovative learning approaches, and a balance between accurate evaluation and realistic workload for teachers.